Structure of 1,5-benzodiazepinones in the solid state and in solution: Effect of the fluorination in the six-membered ring - Pérez-Torralba, Marta; Claramunt, Rosa M.; Ángeles García, M.; López, Concepción; Torralba, M. Carmen; Rosario Torres, M.; Alkorta, Ibon; Elguero, José (Beilstein Journal of Organic Chemistry, 2013)
Two novel tetrafluorinated 1,5-benzodiazepinones were synthesized and their X-ray structures determined. 6,7,8,9-Tetrafluoro-4-methyl-1,3-dihydro-2H-1,5-benzodiazepin-2-one crystallizes in the monoclinic P21/c space group and 6,7,8,9-tetrafluoro-1,4-dimethyl-1,3-dihydro-2H-1,5-benzodiazepin-2-one in the triclinic P−1 space group. Density functional theory studies at the B3LYP/6-311++G(d,p) level were carried out on these compounds and on four non-fluorinated derivatives, allowing to calculate geometries, tautomeric energies and ring-inversion barriers, that were compared with the experimental results obtained by static and dynamic NMR in solution and in solid state.
Keywords: benzodiazepinones; DFT; GIAO calculations; inversion barriers; multinuclear NMR; tautomerism; X-ray structures